Understanding Crassostrea virginica tolerance of Perkinsus marinus through global gene expression analysis - Proestou, Dina A.; Sullivan, Mary E.; Lundgren, Kathryn Markey; Ben-Horin, Tal; Witkop, Erin M.; Hart, Keegan M. (Frontiers in Genetics, 2023)
Disease tolerance, a host’s ability to limit damage from a given parasite burden, is quantified by the relationship between pathogen load and host survival or reproduction. Dermo disease, caused by the protozoan parasite Perkinsus marinus, negatively impacts survival in both wild and cultured eastern oyster (Crassostrea virginica) populations. Resistance to P. marinus has been the focus of previous studies, but tolerance also has important consequences for disease management in cultured and wild populations. In this study we measured dermo tolerance and evaluated global expression patterns of two sensitive and two tolerant eastern oyster families experimentally challenged with distinct doses of P. marinus (0, 106, 107, and 108 parasite spores per gram wet weight, n=3-5 per family per dose). Weighted Gene Correlation Network Analysis (WGCNA) identified several modules correlated with increasing parasite dose/infection intensity, as well as phenotype. Modules positively correlated with dose included transcripts and enriched GO terms indicating increased hemocyte activation and cell cycle activity. Additionally, these modules included G-protein coupled receptor, toll-like receptor, and tumor necrosis factor pathways, which are important for immune effector molecule and apoptosis activation. Increased metabolic activity was also positively correlated with treatment. The module negatively correlated with infection intensity was enriched with GO terms associated with normal cellular activity and growth, indicating a trade-off with increased immune response. The module positively correlated with the tolerant phenotype was enriched for transcripts associated with “programmed cell death” and contained a large number of tripartite motif-containing proteins. Differential expression analysis was also performed on the 108 dosed group using the most sensitive family as the comparison reference. Results were consistent with the network analysis, but signals for “programmed cell death” and serine protease inhibitors were stronger in one tolerant family than the other, suggesting that there are multiple avenues for disease tolerance. These results provide new insight for defining dermo response traits and have important implications for applying selective breeding for disease management.